Biofabrication of titanium dioxide nanoparticles by fungi isolated from soil (Journal of the College of Basic Education, 2022)
In the present study , the biosynthesis of TiO2 nanoparticles were included by fungi Fusarium oxysporum , the particle size were 30-90 nm , fungi Fusarium oxysporum was isolated from soil using serial dilution technique , biomass was harvested and used to biosynthesized TiO2 nanoparticles . The biosynthesis of TiO2 nanoparticles was characterized by UV Vis. Spectroscopy (UV) , X-ray diffraction (XRD) , atomic force microscope (AFM) and scanning electron microscope (SEM) studies .The biosynthesized TiO2 nanoparticles were tested against gram Positive and gram negative bacteria . results showed that TiO2 nanoparticals have a remarkable antibacterial activity against gram Positive and gram negative bacteria .